2023
DOI: 10.3390/catal13020380
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Organic and Inorganic Pollutants to Harmless End Products: Assessment of Practical Application Potential for Water and Air Cleaning

Abstract: It is well-documented that large-scale pollution generated by human activity has a dramatic impact on ecosystems. In this context, removing harmful chemicals via photocatalysis has tremendous potential as a depollution method, utilizing freely available solar light and catalytic materials with low or negligible ecotoxicity. The main drawbacks, which aren’t often addressed in the available literature, are the formation of harmful intermediate products, low reaction rates, limited catalyst stability, and difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(34 citation statements)
references
References 197 publications
0
34
0
Order By: Relevance
“…It is a well-known fact that hydroxyl radicals (OHc), superoxide radicals (cO 2 − ) and holes (h + ) are the main reactive species responsible for the degradation of different types of antibiotics, including NOR. 68,69 To identify the reactive species responsible for the efficient degradation of NOR, additional experiments with quenchers (isopropyl alcohol, ethanol, EDTA-Na 2 p-benzoquinone) were carried out. 70 The photodegradation efficiency of the Cu/Ni 2 O 3 @PC composite in presence of different quenchers of specic reactive species is presented in Fig.…”
Section: Photocatalytic Reaction Mechanismmentioning
confidence: 99%
“…It is a well-known fact that hydroxyl radicals (OHc), superoxide radicals (cO 2 − ) and holes (h + ) are the main reactive species responsible for the degradation of different types of antibiotics, including NOR. 68,69 To identify the reactive species responsible for the efficient degradation of NOR, additional experiments with quenchers (isopropyl alcohol, ethanol, EDTA-Na 2 p-benzoquinone) were carried out. 70 The photodegradation efficiency of the Cu/Ni 2 O 3 @PC composite in presence of different quenchers of specic reactive species is presented in Fig.…”
Section: Photocatalytic Reaction Mechanismmentioning
confidence: 99%
“…44 The rate constant k 1 in eqn ( 14) depends on reaction temperature and the chemical thermodynamic properties of subtracts. [45][46][47] However, several experimental parameters also affected the k 1 value. [48][49][50] Rytwo and Zelkind reported that heterogenous and homogenous photocatalysis could effectively degrade ooxacin when they studied the evaluation of kinetic pseudo-order in the TiO 2 -photocatalyzed degradation of ooxacin.…”
Section: The Pseudo-order Kinetic Modelmentioning
confidence: 99%
“…The tremendous environmental effects, such as climate change, water pollution, and depletion of natural resources caused by industrialization, are linked with an increasing socio-economic demand. The natural world is being severely contaminated by the uncontrolled discharge of many hazardous substances including liquid, semisolid, and solid wastes. , Nowadays, one of our world challenges is the opportunity to get pure water due to pollution. Among the causes of water contamination include energy byproducts, mining operations, insect sides and chemical fertilizers, radioactive wastes, infrastructural activities, and industrial effluents including dyes .…”
Section: Introductionmentioning
confidence: 99%